De l’écriture hybride dans le roman subsaharien de la nouvelle génération - Serghini, Jaouad (2023)
The concept of hybridity continues to challenge researchers in literary and artistic studies. Derived from the field of biology, hybridity recalls the crossing of races and species. Stained with the seal of a curse, hybridity evokes impurity and bastardy. It is thus linked to transgression of the norm, to that which deviates from the natural order. When literary research examines the concept of hybridity, it seeks to identify its aesthetic, artistic, philosophical and political implications, and to study its forms of expression, in the arts and in literature. This study analyzes the concept of hybridity in the new generation of Sub-Saharan Novels. Indeed, the sub-Saharan novel of the 1990s–2020s offers an opportunity to reflect on the question of hybridity within a broad vision that encompasses textuality, intermediality, interartiality and genre.
Keywords: hybridity; intermediality; interartiality; Sub-Saharan novels; intergenericity